Rewarming preterm infants on a heated, water filled mattress. Issue 5 (May 1989) - Sarman, I; Can, G; Tunell, R
Abstract : Sixty low birthweight infants (1000-2000 g) admitted to a neonatal care unit in Turkey were studied. Those not requiring intensive care were randomly assigned for treatment either in a cot on a heated, water filled mattress kept at 37 degrees C (n = 28) or in air heated incubators with a mean air temperature of 35 degrees C (n = 32). On admission 53 (88.3%) of the infants had body temperatures between 30 degrees and 36 degrees C. There was good correlation between axillary and rectal temperatures in the infants while they were hypothermic. Normal temperatures were achieved within the first day and remained within this range during the subsequent days after admission in all the infants treated on the heated, water filled mattress, whereas they were not achieved until three days later in the incubator group. The neonatal mortality among those treated on the heated, water filled mattress was 21%, and among those treated in the incubator 34%. The heated, water filled mattress provides a good alternative to skin to skin contact with the mother, and to the use of a complex and expensive incubator for rapidly attaining and maintaining normal temperatures in the low birthweight newborn.